Dynamics of organic alkalinity in estuarine and coastal environments - Chang‐Ho Lee; Kitack Lee; Joon‐Soo Lee (Limnology and Oceanography, 2025)
The contribution of organic alkalinity ( A DOM ), derived from dissolved organic matter, to coastal acid–base chemistry remains poorly understood, particularly regarding its spatial, seasonal, and compositional variability. This study examines A DOM dynamics across distinct Korean coastal environments, focusing on regional distributions in lagoons, estuaries, and salt marshes with tidal flats, and on year‐round temporal variability in a macroalgal‐dominated habitat. A DOM concentrations ranged from μ mol kg −1 , accounting for less than 2% of total alkalinity ( A T ), while DOC ranged from 51 to 359 μ M. The A DOM –DOC correlation was strong in lagoons and river‐influenced systems ( r > 0.8), but weaker in bays, salt marshes, and macroalgal habitat ( r ~ 0.5–0.7), likely reflecting variability in DOM sources and composition. Back‐titration analysis further revealed consistent acid dissociation constants across regions and seasons, primarily associated with carboxyl (pKa 1 ~ 4.6) and phenolic or amine (pKa 2 ~ 7.0) groups. These two functional groups contributed nearly equally to DOM acid–base behavior across all habitats and seasons, suggesting a shared chemical foundation underlying A DOM despite diverse environmental settings in Korea. These findings provide a mechanistic understanding of how DOM functional group composition governs A DOM across diverse coastal environments.

Synergistic effects of oceanic dimethyl sulfide emissions and atmospheric oxidants on new particle formation in the Arctic - Eunho Jang; Ki-Tae Park; Young Jun Yoon; Kitack Lee; Rita Traversi; Silvia Becagli; Mirko Severi; Peter Tunved; Radovan Krejci; Tae-Wook Kim; Rafael P. Fernandez; Alfonso Saiz-Lopez; et al. (Environmental Research, 2025)

Corrigendum to “Boron to salinity ratios in the Fram Strait entering the Central Arctic: The role of sea ice formation and future predictions” [Marine Chemistry 267 (2024) 104463] - Samantha Rush; Penny Vlahos; Chang-Ho Lee; Kitack Lee; Lauren J. Barrett (Marine Chemistry, 2025)

Quantifying dimethylsulfoniopropionate lyase activity in marine environments using selected ion flow tube mass spectrometry - Ki-Tae Park; Young Jun Yoon; Kitack Lee (Marine Environmental Research, 2025)

Excess alkalinity and its impacts on pCO2 estimation in coastal and estuarine waters of the Yellow Sea - Young Ho Ko; Seung-Hee Shin; Seong-Gil Kim; Mi-Ok Park; Min-Woo Seok; Min-Soo Kim; Kitack Lee; Tae-Wook Kim (Marine Chemistry, 2025)

Persistent organic alkalinity in the ocean - Chang-Ho Lee; Kitack Lee; Joon-Soo Lee; Kwang-Young Jeong; Young-Ho Ko (Geochimica et Cosmochimica Acta, 2024)

Boron to salinity ratios in the Fram Strait entering the Central Arctic: The role of sea ice formation and future predictions - Samantha Rush; Penny Vlahos; Chang-Ho Lee; Kitack Lee; Lauren J. Barrett (Marine Chemistry, 2024)

Significant CO2 emission in the shallow inshore waters of the southeastern Yellow Sea in 2020 - Young Ho Ko; Seung-Hee Shin; Seong-Gil Kim; Mi-Ok Park; Min-Woo Seok; Min-Soo Kim; Kitack Lee; Dongseon Kim; Geun-Ha Park; Tae-Wook Kim (Marine Pollution Bulletin, 2024)

Identifying the external N and Hg inputs to the estuary ecosystem based on the triple isotopic information (δ15NNO3, Δ17ONO3 and δ18ONO3) - Haryun Kim; Hye Seon Kim; Jihee Kim; Dongwoo Yang; Kitack Lee; Kitae Kim; Giyoung Ock; Hyung-Geun Park; Rebecca S. Robinson; Min-Seob Kim; Geun-Ha Park; Ju-Hyoung Kim; et al. (Marine Pollution Bulletin, 2024)

Isotopic investigation of sources and processes affecting gaseous and particulate bound mercury in the east coast, South Korea - Hoin Lee; Sae Yun Kwon; Jonghun Kam; Kitack Lee; Xuewu Fu; In-Gyu Cho; Sung-Deuk Choi (Science of The Total Environment, 2023)

Observational evidence linking ocean sulfur compounds to atmospheric dimethyl sulfide during Icelandic Sea phytoplankton blooms - Kitack Lee; Jun-Seok Kim; Ki-Tae Park; Min-Ji Park; Eunho Jang; Kristinn Gudmundsson; Solveig R. Olafsdottir; Jon Olafsson; Young Jun Yoon; Bang-Yong Lee; Sae Yun Kwon; Jonghun Kam (Science of The Total Environment, 2023)

Microbial alteration in marine sediments: Insights from compound-specific isotopic compositions of amino acids in subseafloor environments - Hyuntae Choi; Bohyung Choi; Yoshito Chikaraishi; Yoshinori Takano; Haryun Kim; Kitack Lee; Dhongil Lim; Kyung-Hoon Shin (Frontiers in Marine Science, 2022)
The proportion of amino acids (AAs) in sediment can be used as an indicator of microbial degradation, which is primarily the product of benthic prokaryote activity. The microbial activity would be reflected with the stable isotope ratio of nitrogen (δ 15 N) at the time of mineralization and resynthesis of AAs. In this study, the compound-specific isotope analysis of individual AAs was used to investigate δ 15 N variation associated with microbial processes in marine sediment samples. Our results showed a decrease in AA concentrations in core-top sediment was accompanied by an increase in δ 15 N values, suggesting large 15 N enrichment in buried AAs. Phenylalanine displayed an increase in δ 15 N from the surface to depths greater than 2 cm, whereas relatively constant δ 15 N values at depths below 2 cm, suggesting that microbial utilization of phenylalanine varies with depth. Glycine showed the highest relative molar contribution (from 12.1 to 36.4%), with the largest δ 15 N increase (from 0.8 to 8.7) in deep sediment, implying that such information can serve as a measure of AA diagenesis in sedimentary environments. Our results also indicated that the δ 15 N values of individual AAs in sediment reflected the microbial alteration of organic matter at water-sediment interfaces and in sub-surface environments. These findings form an important basis for interpreting the δ 15 N values of AAs in sediment.

Factors governing seawater carbonate dynamics in a macroalgal habitat - Ja-Myung Kim; Kitack Lee; In-Seong Han; Miok Kim; Ju-Hyoung Kim; Tae-Hoon Kim; HyunKyum Kim; Byung Hee Jeon; Kyoungsoon Shin (Frontiers in Marine Science, 2022)
Photosynthetic organisms shift the dynamics of surface pCO 2 driven by the sea surface temperature change (thermodynamic driver) by assimilating inorganic C from seawater. Here we measured net C uptake in a macroalgal habitat of coastal Korea for two years (2019-2020) and found that the macroalgal habitat contributed 5.8 g C m −2 month −1 of the net C uptake during the growing period (the cooling period, September−May). This massive C uptake changed the thermodynamics-driven seasonal dynamics such that the air−sea equilibrium of pCO 2 was pushed into disequilibrium. The surface pCO 2 dynamics during the cooling period was mostly influenced by the seasonal decrease in temperature and the proliferation of macroalgae, while the dynamics during the warming period (the stagnant period, June−August) closely followed that predicted based solely on the change in sea surface temperature (thermodynamic driver). In contrast to the phytoplankton-dominated off-shore waters (where phytoplankton populations are large in spring and summer), the impact of coastal macroalgae on surface pCO 2 dynamics was most pronounced during the cooling period, when the magnitude of pCO 2 change was as much as twice that resulting from temperature change. Our study shows that the distinctive features of the macroalgal habitat—in particular the seasonal temperature extremes (~18°C difference), the active macroalgal metabolism, and anthropogenic nutrient inputs—collectively influenced the seasonal decoupling of seawater and air pCO 2 dynamics.

Persistent Continental Shelf Carbon Sink at the Ieodo Ocean Research Station in the Northern East China Sea - Kitack Lee; Ja-Myung Kim; Gyeong-Seok Lee; Eunil Lee; Jin-Yong Jeong; Jaeik Lee; In-Seong Han (Frontiers in Marine Science, 2022)
Hourly (2017–2021) to seasonal (2015–2021) inorganic C data were collected at the Ieodo Ocean Research Station (32.07°N and 125.10°E) in the northern East China Sea (ECS), located under the influence of the nutrient-rich Changjiang Diluted Water (CDW). An increase in phytoplankton biomass from April to mid-August (the warming period) equalized much of the temperature-driven increase in the surface pCO 2 and thus, made the northern ECS a moderate sink of atmospheric CO 2 . From November to March (the cooling period), a large pCO 2 reduction, driven by a temperature reduction, and a high air–sea CO 2 exchange rate, because of high windspeeds, transformed the basin into a substantial CO 2 sink, yielding an annual net C uptake of 61.7 g C m –2 yr –1 . The effects of biological production and temperature change on seawater pCO 2 (and thus, the net air–sea CO 2 flux) were decoupled each season and acted in concert to increase the net annual CO 2 sink by the region. The present study provided the observational and mechanistic lines of evidence for confirming “continental shelf C pump”—a mechanism in the shallow waters of the continental shelves that accumulate a significant amount of C ( via reinforced cooling and promoted biological C uptake) that is transported from the basin surface waters to the interior of the adjacent deep ocean. In the future, an increasing input of anthropogenic nutrients into the northern ECS is likely to make the region a stronger CO 2 sink.

The Diel and Seasonal Heterogeneity of Carbonate Chemistry and Dissolved Oxygen in Three Types of Macroalgal Habitats - Huiru Li; Hanbi Moon; Eun Ju Kang; Ja-Myung Kim; Miok Kim; Kitack Lee; Cheol-Woo Kwak; Haryun Kim; Il-Nam Kim; Ki Yeol Park; Young Kweon Lee; Ji Woong Jin; et al. (Frontiers in Marine Science, 2022)
As concerns about ocean acidification continue to grow, the importance of macroalgal communities in buffering coastal seawater biogeochemistry through their metabolisms is gaining more attention. However, studies on diel and seasonal fluctuations in seawater chemistry within these communities are still rare. Here, we characterized the spatial and temporal heterogeneity in diel and seasonal dynamics of seawater carbonate chemistry and dissolved oxygen (DO) in three types of macroalgal habitats (UAM: ulvoid algal mat dominated, TAM: turf algal mat dominated, and SC: Sargassum horneri and coralline algae dominated). Our results show that diel fluctuations in carbonate parameters and DO varied significantly among habitat types and seasons due to differences in their biological metabolisms (photosynthesis and calcification) and each site’s hydrological characteristics. Specifically, carbonate parameters were most affected by biological metabolisms at the SC site, and by environmental variables at the UAM site. Also, we demonstrate that macroalgal communities reduced ocean acidification conditions when ocean temperatures supported photosynthesis and thereby the absorption of dissolved inorganic carbon. However, once temperatures exceeded the optimum ranges for macroalgae, respiration within these communities exceeded photosynthesis and increased CO 2 concentrations, thereby exacerbating ocean acidification conditions. We conclude that the seawater carbonate chemistry is strongly influenced by the metabolisms of the dominant macroalgae within these different habitat types, which may, in turn, alter their buffering capacity against ocean acidification.

Impact of Sea Ice Melting on Summer Air-Sea CO2 Exchange in the East Siberian Sea - Ahra Mo; Eun Jin Yang; Sung-Ho Kang; Dongseon Kim; Kitack Lee; Young Ho Ko; Kitae Kim; Tae-Wook Kim (Frontiers in Marine Science, 2022)
The role of sea ice melting on the air-sea CO 2 flux was investigated at two ice camps in the East Siberian Sea of the Arctic Ocean. On average, sea ice samples from the two ice camps had a total alkalinity (TA) of ∼108 and ∼31 μmol kg –1 and a corresponding salinity of 1.39 and 0.36, respectively. A portion (18–23% as an average) of these sea ice TA values was estimated to exist in the sea ice with zero salinity, which indicates the excess TA was likely attributed to chemical (CaCO 3 formation and dissolution) and biological processes in the sea ice. The dilution by sea ice melting could increase the oceanic CO 2 uptake to 11–12 mmol m –2 d –1 over the next 21 days if the mixed layer depth and sea ice thickness were assumed to be 18.5 and 1.5 m, respectively. This role can be further enhanced by adding TA (including excess TA) from sea ice melting, but a simultaneous release of dissolved inorganic carbon (DIC) counteracts the effect of TA supply. In our study region, the additional impact of sea ice melting with close to unity TA:DIC ratio on air-sea CO 2 exchange was not significant.

Best Practice Data Standards for Discrete Chemical Oceanographic Observations - Li-Qing Jiang; Denis Pierrot; Rik Wanninkhof; Richard A. Feely; Bronte Tilbrook; Simone Alin; Leticia Barbero; Robert H. Byrne; Brendan R. Carter; Andrew G. Dickson; Jean-Pierre Gattuso; Dana Greeley; et al. (Frontiers in Marine Science, 2022)
Effective data management plays a key role in oceanographic research as cruise-based data, collected from different laboratories and expeditions, are commonly compiled to investigate regional to global oceanographic processes. Here we describe new and updated best practice data standards for discrete chemical oceanographic observations, specifically those dealing with column header abbreviations, quality control flags, missing value indicators, and standardized calculation of certain properties. These data standards have been developed with the goals of improving the current practices of the scientific community and promoting their international usage. These guidelines are intended to standardize data files for data sharing and submission into permanent archives. They will facilitate future quality control and synthesis efforts and lead to better data interpretation. In turn, this will promote research in ocean biogeochemistry, such as studies of carbon cycling and ocean acidification, on regional to global scales. These best practice standards are not mandatory. Agencies, institutes, universities, or research vessels can continue using different data standards if it is important for them to maintain historical consistency. However, it is hoped that they will be adopted as widely as possible to facilitate consistency and to achieve the goals stated above.

Ocean and Atmospheric Observations at the Remote Ieodo Ocean Research Station in the Northern East China Sea - Do-Seong Byun; Jin-Yong Jeong; Duk-jin Kim; Sungmin Hong; Kyu-Tae Lee; Kitack Lee (Frontiers in Marine Science, 2021)
For open ocean environments, it is rare to find continuous, simultaneous air and sea observation records due to the challenges of instrument installation and maintenance. The Ieodo Ocean Research Station (Ieodo ORS), a remote ocean site located in the northern East China Sea with its harsh oceanic and atmospheric environment, provides a platform for the concurrent monitoring of air and sea environments. Since 2014, the Korea Hydrographic and Oceanographic Agency has run the “ Ieodo ORS field trip program ,” via which researchers are able to stay at the station for a week or more. This work reports technical lessons learned over 5 years from five Ieodo ORS research projects launched in 2016. Over the course of these projects, Ieodo ORS has monitored sea surface temperature, temperature and salinity in the water column, seawater pH, air pollutants, and solar radiation. The purpose of this paper is to facilitate the success of future research activities in similar environments by sharing our experiences and “best practices.”

Annual carbon retention of a marine-plankton community in the eutrophic Masan Bay, based on daily measurements - Hae Jin Jeong; Yeong Du Yoo; Kitack Lee; Hee Chang Kang; Jae Seong Kim; Kwang Young Kim (Marine Biology, 2021)

Anthropogenic nitrogen is changing the East China and Yellow seas from being N deficient to being P deficient - Ji‐Young Moon; Kitack Lee; Weol‐Ae Lim; Eunil Lee; Minhan Dai; Yang‐Ho Choi; In‐Seong Han; Kyoungsoon Shin; Ja‐Myung Kim; Jinho Chae (Limnology and Oceanography, 2021)
Addition of the increased anthropogenic nitrogen (NO x and NH y ) emitted from northeast Asian countries to the Yellow and East China seas and coastal waters around Korea has resulted in an unparalleled increase in the nitrate (N) concentration relative to the phosphate (P) and silicate (Si) concentrations in the upper ocean. We found that for the Yellow Sea the increase in N over P was largely explained by increased atmospheric nitrogen deposition, whereas for the northern East China Sea, downstream of the Changjiang River plume, the trend in N increase relative to P was more associated with a change in the combined input of nutrients from atmospheric deposition and riverine discharges. In contrast, the dynamics of the N to P relationship in the southern East China Sea was largely controlled by a change in the intrusion intensity of the Kuroshio Current, which has a low N : P ratio. The disproportionate and persistent input of nutrients to the marine waters of this region over the past four decades has transformed extensive areas from being N deficient to being P deficient, and has concurrently decreased the concentration of Si relative to N. In coastal waters around Korea in particular, these shifts in the nutrient regime have been accompanied by a change from diatom‐dominated to dinoflagellate‐dominated blooms. Given the complexity of coastal ecosystems, the associations between changes in nutrient regimes and biological changes need to be investigated in other coastal areas receiving increasing loads of anthropogenic nitrogen.

The Effects of Ocean Acidification and Warming on Growth of a Natural Community of Coastal Phytoplankton - Bonggil Hyun; Ja-Myung Kim; Pung-Guk Jang; Min-Chul Jang; Keun-Hyung Choi; Kitack Lee; Eun Jin Yang; Jae Hoon Noh; Kyoungsoon Shin (Journal of Marine Science and Engineering, 2020)
An in situ mesocosm experiment was performed to investigate the combined effects of ocean acidification and warming on the coastal phytoplankton standing stock and species composition of a eutrophic coastal area in the temperate-subtropical region. Experimental treatments of natural seawater included three CO2 and two temperature conditions (present control: ~400 μatm CO2 and ambient temperature, acidification conditions: ~900 μatm CO2 and ambient temperature, and greenhouse conditions: ~900 μatm CO2 and ambient temperature +3 °C). We found that increased CO2 concentration benefited the growth of small autotrophic phytoplankton groups: picophytoplankton (PP), autotrophic nanoflagellates (ANF), and small chain-forming diatoms (DT). However, in the greenhouse conditions, ANF and DT abundances were lower compared with those in the acidification conditions. The proliferation of small autotrophic phytoplankton in future oceanic conditions (acidification and greenhouse) also increased the abundance of heterotrophic dinoflagellates (HDF). These responses suggest that a combination of acidification and warming will not only increase the small autotrophic phytoplankton standing stock but, also, lead to a shift in the diatom and dinoflagellate species composition, with potential biogeochemical element cycling feedback and an increased frequency and intensity of harmful algal blooms.

Ichthyotoxic Cochlodinium polykrikoides red tides offshore in the South Sea, Korea in 2014: I. Temporal variations in three-dimensional distributions of red-tide organisms and environmental factors - Hae Jin Jeong; An Suk Lim; Kitack Lee; Moo Joon Lee; Kyeong Ah Seong; Nam Seon Kang; Se Hyeon Jang; Kyung Ha Lee; Sung Yeon Lee; Mi Ok Kim; Ji Hye Kim; Ji Eun Kwon; et al. (Algae, 2017)

Reduction in CO2 uptake rates of red tide dinoflagellates due to mixotrophy - Hae Jin Jeong; Kitack Lee; Yeong Du Yoo; Ja-Myung Kim; Tae Hoon Kim; Miok Kim; Ju-Hyoung Kim; Kwang Young Kim (Algae, 2016)

Species-specific responses of temperate macroalgae with different photosynthetic strategies to ocean acidification: a mesocosm study - Ju-Hyoung Kim; Eun Ju Kang; Matthew S. Edwards; Kitack Lee; Hae Jin Jeong; Kwang Young Kim (Algae, 2016)

Organic alkalinity produced by phytoplankton and its effect on the computation of ocean carbon parameters - Young Ho Ko; Kitack Lee; Ki Hyuk Eom; In‐Seong Han (Limnology and Oceanography, 2016)
In seawater dissolved organic acids produced by phytoplankton dissociate into conjugate bases and an amount of hydrogen ions that maintain electroneutrality, leaving the seawater alkalinity ( A T ) unchanged. However, the resulting conjugate bases react with protons during seawater titration and thereby contribute to the titration alkalinity ( A T−ORG ) whereas the contributions of other species (e.g., , ) to A T are proportionally lowered. Production of such dissolved organic acids was confirmed in each of six phytoplankton cultures and in a coastal environment. In phytoplankton monocultures with initial concentrations of ∼70 μM nitrate and ∼5 μM phosphate, the contribution of organic acids to the seawater alkalinity ( A T−ORG ) was found to be 15−40 μ mol kg −1 on the complete consumption of added nutrients, with the magnitude of A T−ORG depending on the phytoplankton species involved. In the coastal environment the contribution of A T−ORG was as high as 15 μ mol kg −1 . Analysis of back titration data of culture and coastal samples further enabled identification of the functional groups responsible, which included two distinct charge groups (p K a1 = 4.4−4.9; p K a2 = 6.1−6.9). Thus, if the effect of organic acids on seawater A T is not accounted for, the concentrations of inorganic carbon components calculated from pairs of carbon parameters, including A T , will be inaccurate in culture studies and in studies of productive coastal environments.

Synergistic effects of elevated carbon dioxide and sodium hypochlorite on survival and impairment of three phytoplankton species - Keunyong Kim; Kwang Young Kim; Ju-Hyoung Kim; Eun Ju Kang; Hae Jin Jeong; Kitack Lee (Algae, 2013)

Prey‐dependent retention of dimethylsulfoniopropionate (DMSP) by mixotrophic dinoflagellates - Hyunwoo Lee; Ki‐Tae Park; Kitack Lee; Hae Jin Jeong; Yeong Du Yoo (Environmental Microbiology, 2012)
Summary We investigated the retention of dimethylsulfoniopropionate (DMSP) in phototrophic dinoflagellates arising from mixotrophy by estimating the cellular content of DMSP in Karlodinium veneficum (mixotrophic growth) fed for 7–10 days on either DMSP‐rich Amphidinium carterae (phototrophic growth only) or DMSP‐poor Teleaulax sp. (phototrophic growth only). In K. veneficum fed on DMSP‐poor prey, the cellular content of DMSP remained almost unchanged regardless of the rate of feeding, whereas the cellular content of DMSP in cells of K. veneficum fed on DMSP‐rich prey increased by as much as 21 times the cellular concentration derived exclusively from phototrophic growth. In both cases, significant fractions (10–32% in the former case and 55–65% in the latter) of the total DMSP ingested by K. veneficum were transformed into dimethylsulfide and other biochemical compounds. The results may indicate that the DMSP content of prey species affects temporal variations in the cellular DMSP content of mixotrophic dinoflagellates, and that mixotrophic dinoflagellates produce DMS through grazing on DMSP‐rich preys. Additional studies should be performed to examine the universality of our finding in other mixotrophic dinoflagellates feeding on diverse prey species.

Large, non‐Redfieldian drawdown of nutrients and carbon in the extratropical North Atlantic Ocean (46°N): Evidence for dinitrogen fixation? - Geun-Ha Park; Kitack Lee; Rik Wanninkhof; Jia-Zhong Zhang; Dennis A. Hansell; Richard A. Feely (Limnology and Oceanography, 2008)
Considerable drawdown of total dissolved inorganic carbon (C T ) and oversaturation of oxygen (O 2 ) within a cold (15°C) oligotrophic eddy in the extratropical North Atlantic Ocean (46°N, 20.5°W) indicate that, despite the absence of nitrate (NO 3 − ), the eddy was highly productive. Estimates of net community production using the mass balances of C T and O 2 were two to five times greater than those obtained using the mass balance of NO 3 − . The remineralization rates obtained using the integrated rates of C T and NO 3 − accumulation and O 2 utilization for the upper thermocline waters (35‐300‐m depth) were in agreement with C T ‐ and O 2 ‐based net community production over the same period; however, all the estimates exceeded the NO 3 − ‐based net community production by a factor of two to five, pointing to a considerable accumulation of NO 3 − in the upper thermocline in excess of changes in the mixed‐layer NO 3 − inventory. The amount of this excess NO 3 − suggests that a considerable fraction of the net community production was not supported by the mixed‐layer NO 3 − inventory and that an external source of NO 3 − must be present. Of the various mechanisms that might explain the inequity between NO 3 − drawdown in the surface layer and NO 3 − accumulation in the upper thermocline, N 2 fixation is the most viable yet surprising mechanism for producing such excess NO 3 − in this oligotrophic eddy. A significant fraction of net community production in oligotrophic extratropical waters could be supported by processes that are not fully explored or to date have been considered to be insignificant.

Erratum: The effect of seawater CO2 concentration on growth of a natural phytoplankton assemblage in a controlled mesocosm experiment - Ja-Myung Kim; Kitack Lee; Kyoungsoon Shin; Jung-Hoon Kang; Hyun-Woo Lee; Miok Kim; Pung-Guk Jang; Min-Chul Jang (Limnology and Oceanography, 2007)

The effect of seawater CO 2 concentration on growth of a natural phytoplankton assemblage in a controlled mesocosm experiment - Ja-Myung Kim; Kitack Lee; Kyoungsoon Shin; Jung-Hoon Kang; Hyun-Woo Lee; Miok Kim; Pung-Guk Jang; Min-Chul Jang (Limnology and Oceanography, 2006)
We examine the effects of seawater p CO 2 concentration of 25, 41, and 76 kPa (250, 400, and 750 matm) on the growth rate of a natural assemblage of mixed phytoplankton obtained from a carefully controlled, 14‐d mesocosm experiment. Throughout the experiment period, in all enclosures, two phytoplankton taxa (microflagellates and cryptomonads) and two diatom species ( Skeletonema costatum and Nitzschia spp.) account for approximately 90% of the phytoplankton community. During the nutrient‐replete period from day 9 to day 14 populations of Skeletonema costatum and Nitzschia spp. increased substantially; however, only Skeletonema costatum showed an increase in growth rate with increasing seawater p CO 2 . Not all diatom species in Korean coastal waters are sensitive to seawater p CO 2 under nutrient‐replete conditions.

Postindustrial enhancement of aragonite undersaturation in the upper tropical andsubtropical Atlantic Ocean: The role of fossil fuel CO 2 - Sook‐Nye Chung; Geun‐Ha Park; Kitack Lee; Robert M. Key; Frank J. Millero; Richard A. Feely; Christopher L. Sabine; Paul G. Falkowski (Limnology and Oceanography, 2004)
The dissolution of aragonite particles in the ocean primarily depends on the degree of undersaturation of seawater with respect to that mineral. Most of the upper Atlantic Ocean, particularly north of 308S and at depths of less than 2000 m, is supersaturated with respect to aragonite, whereas much of the deep Atlantic is undersaturated. Here we report, for the first time, shallow layers of aragonite‐undersaturated water between 20°S and 15°N in the eastern tropical Atlantic. These layers are centered at 800 m and are surrounded by aragonite‐supersaturated water above and below. This feature most likely results from a combination of chemical and biological processes including the uptake of anthropogenic CO 2 and the oxidation of organic matter falling from the highly productive overlying surface water. Reaction with protons resulting from these processes decreases the carbonate ion concentration and consequently the saturation state of the waters with respect to aragonite. The oceanic uptake of anthropogenic CO 2 during the industrial era has caused a significant increase in the size of the undersaturated layers. Future expansion will likely occur laterally to the west and south, where the degree of supersaturation is low compared to waters to the north. This expansion of the undersaturated layers is a prime example of how human activity during the industrial era has altered the upper ocean chemistry by injecting fossil fuel CO 2 into the ocean.

Global net community production estimated from the annual cycle of surface water total dissolved inorganic carbon - Kitack Lee (Limnology and Oceanography, 2001)
Global net community production is determined, for the first time, from the decrease in salinity (S)ߚnormalized total dissolved inorganic carbon (NC T = C T × 35/S) inventory in the surface mixed layer corrected for changes due to net airߚsea CO 2 exchange and diffusive carbon flux from the upper thermocline. Changes in the mixed layer NC T inventory are estimated using a derived annual cycle of NC T and global records of the mixed layer depth. The annual NC T cycle is deduced from regional algorithms relating NC T to sea surface temperature (SST) and nitrate (NO 3 − ), along with global records of seasonal mean SST and NO 3 − , and from the monthly mean surface partial pressure of CO 2 and total alkalinity fields using thermodynamic models. The two methods show similar regional trends and yield global net community production estimates of 6.7 and 8.0 Gt C (1 Gt C = 1 × 10 12 kg carbon), respectively. The two global estimates are not significantly different and represent an 8–month period of 1990 (warming period) during which the mixed layer NC T concentration decreases. However, the estimates do not account for net community production during a 4–month cooling period. Ratios of net community production during the warming and cooling periods are estimated from multiyear sediment trap data at the Hawaii Ocean Timeߚseries (228N, 1588W) and Ocean Weather Station P (50°N, 145°W) sites. Global extrapolation of these ratios yields annual rates of net community production of 9.1 ± 2.7 and 10.8 ± 2.7 Gt C yr −1 .